Revolt and Hope through Social Media - Ilić, Teodora (Sociološki pregled, 2021)
This paper reviews Castells’s book Networks of Outrage and Hope – Social Movements in the Internet Age which reaffirms the power of new social movements, pointing to their promotion in virtual space and concluding, on the basis of it, about their spontaneity, nonviolence and democracy as inherent characteristics, which can be problematized.
Keywords: Manuel Castells; social movements; social media; “Internet revolutions”; Arab Spring